The Existence of a Utility Function to Represent Preferences - Rader, Trout (Review of Economic Studies, 1963)
Journal Article The Existence of a Utility Function to Represent Preferences Get access Trout Rader Trout Rader New Haven, Connecticut, and Columbia, Missouri Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 30, Issue 3, October 1963, Pages 229–232, https://doi.org/10.2307/2296323 Published: 01 October 1963